Seismic design for reinforced concrete hospital building influenced by soil type and grade of concrete - Anis Farhana, Mazlan (2019)
Seismic design is highly developed, complex, and strictly regulated by codes and standards. Seismic codes present criteria for the design and construction of new structures subject to earthquake ground motions in order to minimize the hazard to life and to improve the capability of essential facilities such as hospital building to function after an earthquake. Current practice in Malaysia does not consider seismic design in designing buildings. Health facilities especially hospitals are exposed to risk, serious damage and loss of life during earthquakes, if not appropriately constructed. Since hospital building is one of significant structure for public necessity as a medical institution and need to accommodate lot of people, it must be able to resist seismic load whenever earthquake happen and it is strongly related with the strength of the structure. Hence, this research investigated the amount of steel reinforcement for reinforced concrete (RC) hospital building with seismic design. The analysis conducted by using three different Soil Type and two different Concrete Grade. There are total of eight models of 8 storey RC hospital building used for the analysis designed based on Eurocode 8 and conducted by using Tekla Structural Design software. Based on the result, it can be concluded that the weight of steel reinforcement for beam and column elements increase around 2.3% to 10.8% when compared to the non seismic design when built using Concrete Grade G30. As for the influenced of Concrete Grade, Concrete Grade G30 required larger amount of steel reinforcement compared to Concrete Grade G40 which is around 12.4% when the structure built on Soil Type C. Thus, Soil Type and Concrete Grade should be taken into consideration for seismic building design.